160 BRONCHIOLITIS AFTER ONE OVERNIGHT USE OF WELL WATER FOR CONTINUOUS POSITIVE-PRESSURE AIRWAY HUMIDIFICATON: WHAT IS IN THE WATER?. Issue 1 (1st January 2007) - Raymond, L. W.; Barkley, J. E.; Langley, R.; Sautter, R.
Abstract : Continuous positive airway pressure (CPAP) humidifiers are a potential source of infection, but a literature review yielded no excess incidence of such. However, a 59-year-old white married interior designer with obstructive sleep apnea (BMI 36.6 kg/m 2 ) became acutely ill after she used well water in a CPAP humidifier one night in her North Carolina mountain home. Otherwise healthy, she used no tobacco, medications, drugs, or alcohol. A sleep study 6 years earlier showed obstructive sleep apnea, so she used CPAP (6 cm H2 O) with humidification only by distilled water. One night she slept for 8 hours on her left side using CPAP with well-water humidification and awakened with severe pain in her upper airway. Over the next week, she had increasing dyspnea. Severe coughing disrupted sleep and produced purulent sputum. Her lungs were clear, and she remained afebrile but weak and bed-bound. Azithromycin (250 mg/day) and hydrocodone cough syrup were prescribed by her family physician. After 2 weeks of cough and dyspnea, crackles developed diffusely over the left lung. O2 saturation was 91%, but chest radiographs were clear. Sputum examination showed 2+ Gram-positive cocci in clusters, but culture yielded only oral flora. No acid-fast or fungal organisms were present on sputum smears, and cultures were negative at 8 weeks. Levofloxacin (750 mg/day for 10 days) yielded no improvement. Methylprednisolone was then given in a tapering dose from 24 mg/day over 6 days followed by prednisone, 10 mg every other day. Crackles and dyspnea decreased during week 5 of the illness, and the patient felt well thereafter except for cough, which persisted through week 8. Repeat O2 saturation was 98% and plain films remained normal. Well water in 2005 contained nitrates, copper, and trihalomethane at levels < 10% of maximum contaminant goals. Filtration (5- and 2-micron commercial string-wound and carbon filters) was used inside the home. Water used to fill the CPAP humidifier had a pH of 7.4 and showed no microorganisms. Levels of 15 metals, 2 halides, and other standard analytes were normal. Conclusion: A single use of filtered well water for CPAP humidification was followed by severe tracheobronchial irritation, dyspnea, weakness, left lung crackles, and impaired oxygenation. We suspect that this illness was bronchiolitis due to well-water contents yet to be identified. The patient has used only distilled-water humidification since her illness began.